Access to Finance and Financial Performance of SMEs in Uganda: A Case Study of Selected SMEs in Eastern Division, Soroti City - Jean Kenneth Ekubu (Uganda Christian University, 2024)
This study sought to examine the effect of access to finance on financial performance of small and medium enterprises in Uganda, a case of selected SMEs in Soroti city, Eastern division. The study objectives were to: To assess the effect of cost of credit and financial performance of SMEs in Soroti city, Eastern division; To examine the effect of collaterals security on financial performance of SMEs in Soroti city, Eastern division; To assess the effect of accessibility of financial institution on financial performance of SMEs in Soroti city, Eastern division. The study population was 120 respondents from the selected SMEs in Eastern division in Soroti City. The study employed purposive sampling and simple random sampling techniques in coming up with a sample size of 92 respondents. The primary data collection method used was a questionnaire. The collected data was analyzed using descriptive statistics in SPSS version 20. Linear and Multiple regression analysis were also used to determine the effect of the independent variables on dependent variables. The study found that cost of credit was significant in predicting the financial performance of SMEs with R square value = 0846 and β = .920 with p-value = 0.000<0.05. The regression coefficient of cost of credit was positive and significant in predicting the financial performance. Further the study found that collateral security had R square value = 0.900 and β = .948 with a p-value = 0.000<0.05. The regression coefficient of collateral security was positive and significant in predicting financial performance. The study further found that Accessibility to financial institutions had significant effect in predicting financial performance with p-values of 0.000 less than 0.05, R square value = 0.812 and β = .901. The study recommends that Financial institutions should also modify their products to suit the financial requirements of small business entrepreneurs. The study additionally suggests that the government should strengthen fiscal policies promoting growth of small business entrepreneurs both for those nursing business ideas and those already in different engagements. Finally, the study recommends that Financial institutions should avail information to people in different areas using the available local channels like radios so that people can quickly get to know about their services rendered.